Efektifitas Peraturan Daerah Nomor 17 Tahun 2005 tentang Bebas Buta Aksara Al-Qur’an pada Usia Sekolah dan Masyarakat Islam di Kelurahan Anawai Kecamatan Wua-wua Kota Kendari dalam Perspektif Hukum Islam - Muhammad Zulkifli La Niasa; Muh. Asrianto Zainal (Institut Agama Islam (IAIN) Kendari, 2021)
This study aims to determine the effectiveness of Regional Regulation No. 17 of 2005 concerning Al-Qur'an Illiteracy Free at School Age and Islamic Society in Kendari City. The results of this study first show that the effectiveness of Regional Regulation Number 17 of 2005 concerning Al-Qur'an Illiteracy Free at School Age and Islamic Society in Wua-Wua District, Kendari City has not been effective. There are 35% of the people of the Wua – Wua District who do not know how to read the Qur'an. In the view of Islamic law, the script of the Qur'an is the book of Allah SWT. which must be preserved because it includes the maintenance of religion. Second, the factors in the process of implementing Regional Regulation Number 17 of 2005 concerning Illiteracy of Al-Qur'an at School Age and Islamic Society in Wua-Wua District, Kendari City are uneven socialization, limited teaching staff, facilities and infrastructure, community legal culture. Third, the solution to the implementation of Regional Regulation Number 17 of 2005 concerning Illiteracy Free Al-Qur'an at School Age and Islamic Society in Wua-Wua District, Kendari City, the government must socialize the regional regulation to all levels of society. The government must prepare facilities and infrastructure to support the effectiveness of local regulations, and the community can increase awareness of the law and the Qur'an, so that the Qur'an is preserved.